Effect of Nadishodhana Pranayama on Cognitive Function amongHealthy Individuals - Anoop, K; Badekar, Vrinda; Bhavana, M (International Research Journal of Ayurveda & Yoga, 2024)
Background & Objectives: The Nadishodhana pranayama, alternate nostril breathing, activates and harmonizes ida and pingala nadis. This study was aimed to evaluate the eﬀect of commonly practiced Nadishodhana pranayama on cognitive functions in healthy individuals.Methods: A randomized control trial of 60 Subjects of age group fulﬁlling inclusion and exclusion criteria were recruited and randomly assigned to Group 1, study group (n=30) and Group 2 control group (n=30). Nadishodhana pranayama training was given for 15 min per session, 6 days per week for the duration of 8 weeks. Pre and Post parameters were recorded. Assessments were done using Cognitive parameters letter cancellation test, trail-making tests A and B (TMT), forward and backward digit spans.Results: The study assessed the eﬀect of NSP on executive functions. The data was tested for normality using the Shapiro-wilks test. Within group comparisons and between groups comparisons were made using paired t test and independent sample test consecutively. Within group comparisons for study group showed a signiﬁcant improvement in Single Letter Cancellation Test (p=0.0028) and digit span forward (p<0.0005). Interestingly there was a signiﬁcant reduction in digit span backward (p=0.005) in the control group. Between group comparisons showed a signiﬁcant improvement in the digit span forward test following the intervention (p=0.003). The results suggest that Nadishodhana pranayama are beneﬁcial for cognitive functions.Interpretation & Conclusion: Nadishodhana pranayama practice is beneﬁcial for improving cognitive functions, Hence Nadishodhana pranayama can be prescribed as eﬀective modality to improve attention and manipulation in auditory working memory.